A cascade bilayer electron transport layer toward efficient and stable Ruddlesden‐Popper perovskite solar cells. (2nd February 2022) - Kim, Kyeong Su; Lee, Woosung; Jung, Jae Woong
Summary: Optimal interfaces play a key role in charge transport/recombination characteristics and minimized potential loss of perovskite solar cells (PSCs). Currently, n ‐type oxide semiconductors are the most common electron transport layer (ETL) material, but the imperfect electronic structure, unfavorable band alignment, and corresponding poor interface of ETL/perovskite absorber remain a great challenge for achieving a high photovoltaic performance of PSCs. Here, we combine a fullerene derivative or a non‐fullerene organic semiconductor with tin(IV) oxide (SnO2 ) to promise much‐improved surface and electronic structure of ETL interface in Ruddlesden‐Popper perovskites (RPPs)‐based photovoltaic devices. The organic semiconductors fill a bumpy surface of SnO2 to make the surface smoother, which effectively avoids the shunt pathways at the interface of the ETL/RPP absorber layer, and thereby suppresses unintended electron‐hole recombination. The organic‐inorganic bilayered ETLs also improve the electronic structure of the SnO2 surface, which provides favorable optoelectronic properties such as quick electron extraction and elongated carrier lifetime in the device. Moreover, the hydrophobic organic semiconductor is helpful in not only growing a uniform, compact, and largely grained RPP absorber layer but also improving the stability of the perovskite absorber layer. Benefiting from the optimized bilayer ETLs, the power conversion efficiency is obviously enhanced up to 10.17% in the RPP‐based photovoltaic devices. More importantly, the bilayer ETLs allow improved long‐term stability in ambient storage of the devices, providing a viable path to design practical interfaces of efficient and stable RPP‐based PSCs. Highlights: Hybrid bilayer electron transport layer is designed to enhance the efficiency of Ruddlesden‐Popper perovskite solar cells. Phenyl‐C61‐butyric acid methyl ester and ITIC are inserted as n ‐type organic semiconductors onto SnO2 film for the bilayer electron transport layer. Tailored optoelectronic properties of the bilayer electron transport layers deliver 10.17% efficiency of Ruddlesden‐Popper perovskite solar cells. Abstract : A hybrid bilayer electront ransport layer (ETL) structure is designed to optimize and improve optoelectronic properties of interface of 2D Ruddlesden–Popper perovskites ‐based solar cells. The n ‐type organic semiconductors inserted onto the SnO2 ELT effectively passivate defective sites and oxygen vacancy antisites at the interface, attaining efficient electron transport and carrier recombination blocking within the devices. In addition, the organic semiconductors on SnO2 afford more hydrophobic surface, resulting in outstanding long‐term stability of the device in ambient atmosphere up to >300 hours.